2021
DOI: 10.3390/v13010123
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Transmission of Zika Virus Through Breast Milk and Breastfeeding: A Systematic Review of the Evidence

Abstract: We systematically searched regional and international databases and screened 1658 non-duplicate records describing women with suspected or confirmed ZIKV infection, intending to breastfeed or give breast milk to an infant to examine the potential of mother-to-child transmission of Zika virus (ZIKV) through breast milk or breastfeeding-related practices. Fourteen studies met our inclusion criteria and inform this analysis. These studies reported on 97 mother–children pairs who provided breast milk for ZIKV asse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Among exposed fetuses, fetal loss occurred in 14% and severe complications compatible with Congenital Zika Syndrome (CZS) occurred in 21% [ 221 ]. To date, although ZIKV particles have been detected in human milk, breastfeeding has not been confirmed as a transmission route and mothers with possible or confirmed ZIKV infection are recommended to keep breastfeeding their babies [ 223 ]. Mechanisms of fetal damage …”
Section: Zika Virusmentioning
confidence: 99%
“…Among exposed fetuses, fetal loss occurred in 14% and severe complications compatible with Congenital Zika Syndrome (CZS) occurred in 21% [ 221 ]. To date, although ZIKV particles have been detected in human milk, breastfeeding has not been confirmed as a transmission route and mothers with possible or confirmed ZIKV infection are recommended to keep breastfeeding their babies [ 223 ]. Mechanisms of fetal damage …”
Section: Zika Virusmentioning
confidence: 99%
“…Since the 2007 outbreak, it has repeatedly been suggested that ZIKV can be transmitted to newborns through breastfeeding [ 12 ]. However, since several case reports described no transmission of ZIKV from infected mothers to their newborn [ 26 ], biological factors regulating the efficiency of this route of transmission might exist (viral load, viral form, immunological status, stage of lactation, breast milk composition, etc.). We investigated the role of breast milk and its components in viral transmission using a well-described animal model for ZIKV infection: A129 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although cases of probable transmission of ZIKV from infected mothers to breastfed newborns have been reported [ 12 ], other case reports showed a lack of transmission by breastfeeding [ 26 ]. Therefore, biological or genetic factors controlling the transmission should be investigated (viral load, viral form, immunological status, stage of lactation, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…The primary mode of ZIKV acquisition is through the bite of the Aedes aegypti mosquito [ 16 ], or through vertical transmission from an infected mother. Although the virus has been detected in breast milk of infected mothers, clinical data demonstrating transmission via breast milk to the infant is lacking [ 17 ]. Sexual transmission [ 18 ] and acquisition via solid organ or blood transfusions are well-described [ 19 ].…”
Section: Zika Virusmentioning
confidence: 99%